REDUCING THE INTERMITTENCE OF RENEWABLE ENERGY SOURCES WITH SEASONAL-PUMPED-STORAGE PLANTS - Machado, Pedro P. B.; Tenaglia, Gustavo C.; Hunt, Julian D.; Ramos, Dorel S.; Junior, Amaro O. P. (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This paper presents a computational method to model and evaluate if Pumped Storage Plants (PSP) have the potential to reduce the intermittency of wind generation from different sites in Brazil and to improve the operation efficiency of hydroelectric plants in cascade. Since the problem to be solved does not have a defined analytic solution, a Stochastic Optimization Algorithm was implemented to reach an optimal solution to the set of equations, inputs and proposed scenarios. A case study was developed based on the Paraná River Basin and the results shows that the model can operate in a variety of different operational patterns, making feasible the evaluation of different hydrological and wind scenarios and to assume different PSP storage and generation capacities and allowing the comparison between the efficiency improvement of a conventional Pumped-Storage and a Seasonal-Pumped-Storage in the same scenario. The study concludes that a PSP can effectivity reduce the intermittency of wind and solar sources and contribute to the optimization of the Brazilian electricity sector.